Eficácia ou simbolismo? uma análise das medidas protetivas de urgência na Lei Maria da Penha - Mezzari, Luís Gustavo (Universidade do Vale do Rio dos Sinos, 2019)
By the dichotomous analysis between the efficacy and symbolism of the urgent protective measures, it is possible to verify that this precautionary instrument demonstrates certain weaknesses when put into practice, which results in vulnerability to the victims of gender-based violence. However, although they demonstrate utopianism in its dispositions and objectives, urgent protective measures appear as a capable method of inhibiting new violent events perpetrated by the aggressor against his partner, ex-partner and/or family member. But, in order to arrive at such a conclusion, it is necessary to analyze the statistics collected, the doctrinal teachings on the subject and the opinions given by professionals working in court lawsuits related to the rite of the Maria da Penha Law, as a way of meticulously answering the questioning, which is to understand the urgent measures of protection as a capable mechanism to provide greater protection to the victims of gender-based violence that holds them in their power or as a symbolic element integral to the unbridled wave of expansion of criminal law. The research method employed is hypothetical-deductive. The research technique used was bibliographical and documentary analysis.
Keywords: Violência de gênero; Medidas protetivas de urgência; Lei Maria da Penha; Eficácia; Simbolismo; Gender violence; Urgent protective measures; Maria da Penha Law; Efficiency; Symbolism